Monitoramento de borboletas frugívoras no Parque Estadual Carlos Botelho, SP - Almeida, Alicia Antonioli (2023)
Environmental monitoring through animals is widely used in Conservation Units, in order to diagnose the quality of the environment and intervene if necessary. The choice of indicator species should be based on its ecological response to changes in the ecosystem so that it can expose the reality of the environment in which it is inserted. Fruit-eating butterflies represent one of the most used groups for biomonitoring since they are abundant and have low-cost sampling, such as through transects. Therefore, the purpose of this study was to analyze the degree of conservation of internal areas of the Carlos Botelho State Park (CBST), SP with different uses through the Biodiversity Monitoring Program with fruit-eating butterflies. For this purpose, the data was obtained by capturing Lepidoptera of different tribes in 48 traps strategically positioned in three transects, two on the park road and one on the internal road of the CBST. The samplings occurred in January and February 2022. Forty-eight butterflies were counted in total, with a significant representation of individuals from the Satyrini and Brassolini tribes in all transects. Their composition, however, reflects the different conservation statuses of the areas. Specimens of the Satyrini tribe were sampled with greater abundance in open and more anthropized environments (park road) and a greater abundance of specimens of the Brassolini tribe in more conserved environments of continuous forest (road-internal). The Carlos Botelho State Park repeats the same distribution pattern already detected in other CUs in the State of São Paulo participating in this monitoring program, highlighting the importance of continuing this program to understand how the use of the Park affects sensitive populations, in addition to enabling the proposal of measures aimed at mitigating the damage that may be occurring in the internal areas of the Conservation Unity.